Financial performance and socio-emotional wealth in small and medium-sized family and non-family enterprises - Esparza-Aguilar, José Luis (2021)
The business where family members participate in its ownership and management, and there is a will for continuity is known as a family business. One of its distinctive features is the pursuit of both economic and non-economic interests. For this reason, the notion of performance in the family business is more complex, and its study is still scarce. The objective of this work was to analyze financial performance and socio-emotional wealth in Mexican family and non-family business. To achieve it, a survey was  applied to a sample of 585 companies installed in the states of Tamaulipas, Puebla, and Quintana Roo, Mexico. The questionnaire was exclusively addressed to its managers or owners. The data were analyzed through descriptive and univalent statistical techniques. The results highlight significant differences between Mexican family business and non-family business.